Diagnostic utility of p16 immunocytochemistry in metastatic cervical lymph nodes in head and neck cancers. Issue 4 (11th January 2021) - Kapoor, Dimple; Handa, Uma; Kundu, Reetu; Das, Arjun
Abstract: Background: Human papilloma virus (HPV) testing can be useful in work‐up of patients presenting with cervical node metastasis, suspected to be of head and neck origin as HPV positive tumors show better response to therapy. The current study was planned to detect HPV in aspirates from metastatic cervical nodes using p16 immunocytochemistry in head and neck squamous cell carcinoma (HNSCC). Further correlation of HPV status between node metastasis and primary tumor was done. Methods: The prospective study included 50 patients diagnosed as metastatic SCC in cervical nodes on fine needle aspiration with either known head and neck primary or primary detected post cytodiagnosis. Immunostaining for p16 was carried out on both smears and tissue sections. Results: Forty‐three patients were male and seven were female. Age of the patients ranged from 35 to 80 years. Primary sites of HNSCC were oropharynx (25), oral cavity (14), and larynx (11). Immunocytochemistry for p16 on smears showed positivity in 28 cases. Immunohistochemistry for p16 in primary tumors was positive in 34. There was substantial agreement between p16 immunocytochemistry and immunohistochemistry (Kappa value: 0.823). The sensitivity of p16 immunocytochemistry for the detection of HPV in metastatic HNSCC was 82.4% while the specificity was 100%. The positive and negative predictive values were 100% and 72.7%, respectively. Conclusions: P16 immunocytochemistry in HNSCC metastatic to cervical node mirrors the HPV status of the corresponding primary tumor. Hence in tumors of unknown origin presenting as cervical node metastasis, p16 immunocytochemistry can be employed for localization of the primary.